The Prevalence of Polycystic Ovary Syndrome, Its Phenotypes and Cardio-Metabolic Features in a Community Sample of Iranian Population: Tehran Lipid and Glucose Study - Farhadi-Azar, Mahbanoo; Behboudi-Gandevani, Samira; Rahmati, Maryam; Mahboobifard, Fatemeh; Khalili Pouya, Ensi; Ramezani Tehrani, Fahimeh; Azizi, Fereidoun (Frontiers in Endocrinology, 2022)
Objectives: we aimed to evaluate the prevalence of polycystic ovary syndrome (PCOS), phenotypical and its cardio-metabolic features in comparison to healthy eumenorrheic, nonhirsute women without polycystic ovaries. The second aim was to assess the cardio-metabolic characteristics of women who suffered from one criteria of PCOS compared to those healthy women. Methods: In this cross-sectional population-based study, a total of 1960 eligible women aged (18–45 years) were recruited from among Tehran-Lipid and Glucose-Study participants and were classified as the three groups of women with PCOS by Rotterdam criteria, non-PCOS women with one criteria of PCOS and healthy eumenorrheic, nonhirsute women without PCOM as control group. Further PCOS women were extended to four phenotypes of A-D. Cardio-metabolic profiles and the prevalence of comorbidities of metabolic syndrome and dyslipidemia among these groups were compared regression models adjusted for age and body mass index. Results: The prevalence of PCOS were 19.4%, among them and 23.9%, 46.3% ,21.5% and 8.1 % had phenotype A, B,C and D, respectively. Among remaining 1580 women who did not fulfill the PCOS criteria, 108 (6.8%) suffered from only oligo/anovulation, 21% only hyperandrogenism/hyperandrogenemia, 16.2% only PCOM in ultrasound and 62% were healthy women. Results of study revealed that some adiposity indices and lipid abnormalities in PCOS phenotypes with hyperandrogenism (A, B and C) were worser than healthy women. Women classified as phenotype D did not differ from healthy ones in term of adiposity and lipid abnormalities. However, the respective values for other cardiometabolic profile and metabolic syndrome (MetS) rate in different phenotypes of PCOS were similar to healthy women. There were not statistically significant differences between participants with one criteria of PCOS and healthy counterparts in the term of most adiposity indexes, cardio-metabolic factors and also comorbidities of metabolic syndrome. Conclusion: PCOS mainly classical phenotypes A and B are common among Iranian women of reproductive age. Women with PCOS who had androgen access exhibit the worst lipid profile and those who had all three components of the syndrome showed the higher rate of MetS. characteristics, when compared to healthy subjects.